The Hymnography in Honour of Saints Constantine and Helena and its Connection with Imperial Ideology - Nikolaou, Anastasia (Studia Ceranea, 2023)
This article presents an overview of published and unpublished Byzantine and post-Byzantine hymnographic texts dedicated to Saint Constantine, founder of Constantinople and first Byzantine emperor, and his mother Saint Helena. Specifically, we cite and comment upon some indicative passages primarily found in canons of the Matins, which refer to historical events from the lives of the saints and attribute to them, especially to Saint Constantine, virtues such as justice, piety, wisdom, and the defense of the true faith. These qualities are directly associated with the imperial political ideology as this was shaped principally by Eusebius of Caesarea in his works Life of Constantine and Tricennial Oration.